(3GdeZfj aj TQM ehLR GdbGfhf aj GdWH dGHf GdfajSs - (3SjO GdOjf GdcGRQhfis; (3Ydj Hf CHj GdMRe GdbQTj , YdGA GdOjf CHh GdMSf , GHf GdfajS,J (B687 (3g` s ((3MSjf Hf jhSa s)
(3ChdgG (B:s
(3gPG hdeG QCjJ GdeNJUQ GdPi Cdag GdeYQha HGHf GdfajS hSeGg HGdehLR cbGfhf hOSJhQ ddeJWHHjf CQOJ JhVjM HYV ehGVYg s
(3BNQgG (B:s
(3hef TQM GdbGfhf hCUd Gdcd ef fUhU GdbGfhf ,aEfg bO LeY ajg RHOI cdGe GdMceGA hdHGHgG hcPdc bO GYJeOJ Ydjg ai CcKQ GdehGVY cd GdGYJeGO s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B58s
Keywords: (3GdWHs